Bleeding Complications in Patients Undergoing Celiac Plexus Block. Issue 4 (July 2016) - Warner, Nafisseh S.; Moeschler, Susan M.; Warner, Matthew A.; Hoelzer, Bryan C.; Eldrige, Jason S.; Bendel, Markus A.; Mauck, William D.; Watson, James C.; Gazelka, Halena M.; Lamer, Tim J.; Kor, Daryl J.; Hooten, William Michael
Abstract : Background and Objectives: Celiac plexus blockade has known risks including bleeding and neurologic injury because of the close proximity of vascular and neuraxial structures. The aim of this study was to determine the incidence of bleeding complications in patients undergoing celiac plexus block (CPB), with an emphasis on preprocedural antiplatelet medication use and coagulation status. Methods: This is a retrospective study from 2005 to 2014 of adult patients undergoing CPB by the pain medicine division at a tertiary care center. The primary outcome was red blood cell (RBC) transfusion within 72 hours of needle placement, with a secondary outcome of bleeding complications requiring emergency medicine, neurology, or neurosurgical evaluation within 31 days. Results: A total of 402 procedures were performed on 298 unique patients, with 58 patients (14.4%) receiving aspirin or nonsteroidal anti-inflammatory drugs (NSAIDs) preoperatively. Five patients (1.2%) received RBC transfusion within 72 hours, of which one had received preprocedure NSAIDs. A platelet count measured within 30 days was available for 268 patients, with 7 patients (2.6%) having platelet counts of 100 × 10 9 /L or less at the time of needle placement. A total of 187 patients had a valid preoperative international normalized ratio (INR), with 9 (4.8%) having an INR of 1.5 or higher (range, 1.5–2.6). One patient (11.1%) required RBC transfusion compared with an RBC transfusion rate of 2.3% (4 of 178) in those with normal INR ( P = 0.221). We identified no bleeding complications requiring emergency medicine, neurology, or neurosurgical evaluation. Conclusions: This study suggests that CPBs may be safely performed in patients receiving aspirin and/or NSAID therapy.